Ectopic Expression of Innate Immune Protein, Lipocalin-2, in Lactococcus lactis Protects Against Gut and Environmental Stressors. Issue 7 (25th April 2017) - Saha, Piu; Chassaing, Benoit; Yeoh, Beng San; Viennois, Emilie; Xiao, Xia; Kennett, Mary J.; Singh, Vishal; Vijay-Kumar, Matam
Abstract : Background: Lipocalin-2 (Lcn2) is a multifunctional innate immune protein that exhibits antimicrobial activity by the sequestration of bacterial siderophores, regulates iron homeostasis, and augments cellular tolerance to oxidative stress. Studies in the murine model of colitis have demonstrated that Lcn2 deficiency exacerbates colitogenesis; however, the therapeutic potential of Lcn2 supplementation has yet to be elucidated. In light of its potential mucoprotective functions, we, herein, investigated whether expression of Lcn2 in the probiotic bacterium can be exploited to alleviate experimental colitis. Methods: Murine Lcn2 was cloned into the pT1NX plasmid and transformed into Lactococcus lactis to generate L. lactis– expressing Lcn2 (Lactis-Lcn2) or the empty plasmid (Lactis-Con). Lactis-Lcn2 was characterized by immunoblot and enzyme-linked immunosorbent assay and tested for its antimicrobial efficacy on Escherichia coli . The capacity of Lactis-Lcn2 and Lactis-Con to withstand adverse conditions was tested using in vitro viability assays. Dextran sodium sulfate colitis model was used to investigate the colonization ability and therapeutic potential of Lactis-Lcn2 and Lactis-Con. Results: Lcn2 derived from Lactis-Lcn2 inhibited the growth of E. coli and reduced the bioactivity of enterobactin ( E. coli– derived siderophore) in vitro. Lactis-Lcn2 displayed enhanced tolerance to adverse pH, high concentration of bile acids, and oxidative stress in vitro and survived better in the inflamed gut than Lactis-Con. Consistent with these features, Lactis-Lcn2 displayed better mucoprotection against intestinal inflammation than Lactis-Con when administered into mice with dextran sulfate sodium–induced acute colitis. Conclusions: Our findings suggest that Lcn2 expression can be exploited to enhance the survivability of probiotic bacteria during inflammation, which could further improve its efficacy to treat experimental colitis.